2005
DOI: 10.1007/s10641-005-2196-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in life-history traits in two clonal strains of the self-fertilizing fish, Rivulus marmoratus

Abstract: SynopsisWe compared life-history traits such as fecundity, sex ratio, reproductive cycle, age at sexual maturity, embryonic period, egg size, early growth and morphology in two clonal strains (PAN-RS and DAN) of the mangrove killifish (Rivulus marmoratus) under constant rearing conditions. We found a positive relationship between growth and reproductive effort. Fecundity was significantly higher in the PAN-RS strain than in the DAN strain. Sex ratio was significantly different, with DAN producing more primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…As predicted, adults released more embryos in air relative to water, suggesting a preference for terrestrial environments. The clutch size was relatively low, consistent with previous reports in K. marmoratus (0.7-2.2 embryos per week; Grageda et al, 2005). Previous literature described anecdotal observations of adult K. marmoratus that released embryos terrestrially in a terrarium (Abel et al, 1987;Taylor, 1990) or in the wild near crab burrows (Taylor, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…As predicted, adults released more embryos in air relative to water, suggesting a preference for terrestrial environments. The clutch size was relatively low, consistent with previous reports in K. marmoratus (0.7-2.2 embryos per week; Grageda et al, 2005). Previous literature described anecdotal observations of adult K. marmoratus that released embryos terrestrially in a terrarium (Abel et al, 1987;Taylor, 1990) or in the wild near crab burrows (Taylor, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…They showed that this species secretes estrogen (17β-estradiol), androgen (11-ketotestosterone), and progestin (17α-20β-dihydroxy-4-pregnen-3-one) synchronously, which is unusual in teleosts. Moreover, the mangrove killifish does not have clear diel rhythms in terms of spawning and ovulation (Grageda et al 2005). Therefore, the triggering mechanisms of ovulation, self-fertilization, and spawning (oviposition) are still unclear and will be the subject of future research.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to assess the exact fertilization time of K. marmoratus embryos, as ovulated eggs are fertilized within the gonadal lumen (Sakakura et al, 2006). Thus, all timings expressed as hours post fertilization are back-calculated estimations based on previous literature (Koenig and Chasar, 1984;Grageda et al, 2005).…”
Section: Experimental Procedures Experimental Animalsmentioning
confidence: 99%